The power of Bamum writing struggling with colonization : semiotic and historical approach. - (:unkn) unknown (My University, 2024)
Upon ascending to power after a civil war, Ibrahim Njoya, King of the Bamum people, seeks to solidify his authority within his kingdom, located in what is now western Cameroon. To do so, he finds the perfect tool in the invention of his own writing system. This thesis examines Bamum script as an instrument of power, drawing on Claude Lévi-Strauss’s theory of writing as a means of subjugation and structuring social relations. Confronted with internal challenges and European colonization, Njoya designs a unique script for the Bamum kingdom, developing an 80-symbol syllabary from the late 18th century through the 1910s. By transcribing laws, historical narratives, and spiritual values, Njoya transforms this script into a political tool that legitimizes his authority and centralizes power.Following Lévi-Strauss’s analysis, this research demonstrates how Bamum script transcends simple communication to organize Bamum society as a tool for governance and control. Within a context of triple influence—Arabic, Latin, and Bamum—Njoya chooses to reject external scripts to assert linguistic and cultural sovereignty in the face of colonizers. Beyond its function of emancipation, the script becomes an instrument of subjugation in the Lévi-Straussian sense, enabling Njoya to unambiguously convey his laws, history, and political will to his people. From a king threatened by civil war, he becomes, through his reign and use of his writing system, the most legitimate of sovereigns.Methodologically, the analysis combines a historical study of the relations between the Bamum kingdom and colonial powers with a semiotic reading of Bamum pictograms. This intersection shows how writing, by fixing narratives and laws, consolidates Njoya’s power while resisting French domination, up until the script’s prohibition by colonial authorities. In this way, the thesis provides a concrete illustration of Lévi-Strauss’s theory within a unique African colonial context, hi
Keywords: African Research